2018
DOI: 10.1038/s41598-018-25442-4
|View full text |Cite
|
Sign up to set email alerts
|

Automatic detection advantage of network information among Internet addicts: behavioral and ERP evidence

Abstract: Converging evidence has proved the attentional bias of Internet addicts (IAs) on network information. However, previous studies have neither explained how characteristics of network information are detected by IAs with priority nor proved whether this advantage is in line with the unconscious and automatic process. To answer the two questions, this study aims to investigate whether IAs prioritize automatic detection of network information from the behavior and cognitive neuroscience aspects. 15 severe IAs and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 81 publications
5
11
0
Order By: Relevance
“…He et al (62) used the reversed deviant-standard oddball paradigm to investigate the automatic detection advantage of Internet addicts (IAs) toward Internet-related pictures and found that Internet-related pictures elicited larger MMN amplitude in the IA group than that in the control group. They also found that Internet-related pictures elicited larger MMN amplitude than the neutral pictures in the IA group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…He et al (62) used the reversed deviant-standard oddball paradigm to investigate the automatic detection advantage of Internet addicts (IAs) toward Internet-related pictures and found that Internet-related pictures elicited larger MMN amplitude in the IA group than that in the control group. They also found that Internet-related pictures elicited larger MMN amplitude than the neutral pictures in the IA group.…”
Section: Discussionmentioning
confidence: 99%
“…Functional magnetic resonance imaging studies have shown that the brain reward system of individuals with IGD exhibits an increased degree of activation in response to addiction-related cues (6669). Following the incentive-sensitization model, He et al (62) believed that long-term Internet addiction behavior changes the function of IAs' brain system related to the reward circuit so that the reward circuit gradually shows increased sensitivity to Internet-related cues. This neural sensitization in turn leads to Internet-related cues becoming a salient incentive.…”
Section: Discussionmentioning
confidence: 99%
“…It has even been claimed that epigenetic mechanisms may come into play here, leading to an atrophying of our powers of memory and a reduction of our attention span; we are also negatively impacted by the demands of engagement in multitasking, icon-based communication, and extensive possibilities for psychological disturbance, with Internet Addiction Disorder (IAD) becoming a recognized mental problem. All these consequences of the intensive use of digital technology reinforce the need for the scientific investigation of what happens to Internet users following such a massive insertion of digital technology into their lives [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…He et al. (2018) provided evidence for this bias at the behavioral and cognitive neural levels. At the behavioral level, the researchers used a visual dot‐probe masking paradigm and found that individuals with IGD showed significantly faster reaction times when probing dots were consistent with Internet‐related pictures, whereas healthy individuals showed no significant reaction time differences for probing dots in the consistent versus inconsistent condition.…”
Section: Introductionmentioning
confidence: 98%
“…Some researchers have further found that the cognitive processing bias of individuals with IGD for Internet gaming cues is based on an automatic detection bias for gaming‐related cues (He et al., 2018). According to incentive‐sensitization theory (Franken, 2003; Robinson & Berridge, 1993), long‐term repeated online gaming behavior alters neuronal circuits associated with motivation and reward processing in the neural system of individuals with IGD (Ko et al., 2013; Sun et al., 2012), which makes the reward center progressively more sensitive to game‐related features, resulting in increased automatic detection of related features.…”
Section: Introductionmentioning
confidence: 99%